Career Women's Communication Patterns in Maintaining Family Harmony in The Office of The Ministry of Religion Medan City - Raudhatul Jannah; Rahmanita Ginting (Universitas Medan Area, 2023)
The purpose of this study was to analyze the communication patterns and barriers of career women in maintaining family harmony in the office of the Ministry of Religion of Medan City. The theory used is Interpersonal Communication, Communication Patterns, Family Communication, Family Harmony, and Affection. The method used is a qualitative approach. The research subjects are women who work at the Ministry of Religion office in Medan City and have been. Data collection techniques were carried out through observation and interviews. The results showed that the communication pattern used was transactional, namely the occurrence of exchanging ideas between partners, so that it could be accepted by each party; Barriers faced in family harmony, namely being very rarely in the house because part of the time is used to work outside the home. Thus, women's attention to careers for children is very limited. The implications can have an impact on the mental development of children who are not good. The high busyness can also interfere with health, and cause the household situation to become inconsistent. Meanwhile, the informant chose to become a career woman to help the family's economy. The reason for this is that the necessities of life are currently getting higher.